Student’s Perceptions of Using TED Talks to Improve EFL Speaking Skill - Kusumastuty, Patria Erry; Mulyono, Herri; Ekawati, Anita Dewi (UICELL, 2019)
This quantitative study investigated the students? perception of using TED Talks to improve their speaking skill. The study drew upon 210 in-service EFL scholar across universities in fourteen provinces in Indonesia. These student participants were asked to complete seventeen items of close-ended questionnaire. Statistical data analysis using reliability, descriptive analysis and One-Way ANOVA were performed using SPSS software. The findings revealed two students? perceptions about using TED Talks, there were positive and negative perceptions. The results were performed with differences between gender and age as demographic. Keywords: TED Talks, Speaking Skill